Local Wisdom of Natural Resource Management in Communities Around the Mine in Central Halmahera Regency - M. Ridha Ajam; Irfan Ahmad; Andi Sumarkarman; Safrudin Abdulrahman; Bahtiar Hairullah (Journal of Social Science, 2023)
The main problems of this research include two things, namely: (1) what local wisdom is related to the management of natural resources owned by the mining circle community in Central Halmahera Regency, and (2) how is the existence of the local wisdom of the mining circle community in managing natural resources? nature in Central Halmahera Regency. This study uses a qualitative approach that collects through document studies (literature review), observations (observations), and in-depth interviews. Research informants are people who live in the mining area which are determined by purposive sampling based on their knowledge and experience related to the research topic. The data collection locations were in the Central Halmahera Regency area covering two sub-districts, namely North Weda and Central Weda Districts. The results of the study show that the communities around the mines in Central Halmahera Regency classify natural resources based on where or where the resources are located, namely resources that are on the mainland. In managing these various natural resources, communities around mining have various traditions that can be seen as a form of local wisdom. The entry of the mining industry into Central Halmahera Regency has no more positive impacts than the negative effects it produces. Mining companies are seen by residents as 'giants' that destroy water sources that are vital for residents' lives so that they can no longer be used. In its development, the presence of mining companies, especially PT. IWIP, influences the existence of local wisdom in the communities in the study locations related to the management of their natural resources.